Absorptive Capacity in Inbound and Outbound Open Innovation in Emerging Economy context - Manosalvas Vaca, Carlos A.; Manosalvas Vaca, Luis; Guerrero Bejarano, María Auxiliadora; Silva Siu, Daniel Ricardo (Revista Venezolana de Gerencia, 2023)
The knowledge society is characterized by competitive and complex business environments, a situation that forces companies to develop permanent innovation processes to generate competitive advantages that allow them to survive in a new business environment. In response to this premise, dynamic capabilities and specifically Absorptive Capacity (ACAP), is the most relevant capacity to obtain higher levels of organizational performance. In this context, this study analyzed whether ACAP influences the development of inbound and outbound open innovation. Through surveys directed at 252 managers of SMEs that offer technology services in an emerging economy, and using the PLS-SEM technique, it was evidenced that ACAP has a positive relationship with Inbound and Outbound Open Innovation. The results reveal that the application of innovation models requires the development of dynamic capabilities, mainly absorptive capacity, with four of its components: assimilation, acquisition, transformation and exploitation. Organizations must adopt strategies to correctly detect and absorb external knowledge in order to establish an adequate connection with internal knowledge and, in this way, take advantage of the benefits inherent to open innovation.